Retrospective Analysis of a Multicenter Observational Study of the Relationship Between Social Determinants of Health and Complications After Children’s Heart Surgery - Khurram Mustafa, FRCPCH; Christopher Leahy, PhD; Deborah Ridout, MSc; Katherine L. Brown, MD (Critical Care Explorations)
IMPORTANCE:. Epidemiological studies have highlighted disparities in illnesses and outcomes for critically unwell children. OBJECTIVES:. We aimed to describe social characteristics and explore links with the outcome of postoperative complications with children’s heart surgery. DESIGN, SETTING, AND PARTICIPANTS:. Retrospective analysis of a multicenter observational dataset including those under 17 years old undergoing heart surgery from October 2015 to June 2017 at five U.K. children’s cardiac centers. MAIN OUTCOMES AND MEASURES:. Univariate and multivariable multinomial regression analyses were undertaken for the outcome of predefined postoperative complications. RESULTS:. Of 2898 cases meeting criteria, 2708 had complete data. Two thousand one hundred three (77.66%) had no complications, 369 (13.62%) had a single complication, 56 (2.06%) received Extracorporeal Life Support, and 179 (6.61%) had multiple complications. Children residing in low deprivation neighborhoods were under-represented: lowest quintile 361 (13.33%). Minoritized ethnic group was strongly linked to indices of deprivation: residence in neighborhoods with highest deprivation occurred with Bangladeshi, Black African, and Pakistani ethnicity and lowest deprivation with White ethnicities. Adjusted for clinical risk factors compared with the reference group (White), patients from Asian background had a significantly higher risk of developing single vs. no complications (odds ratio [OR], 1.53; 95% CI, 1.00–2.32) and Black patients had a higher risk of developing multiple vs. no complications (OR, 2.19; 95% CI, 1.09–4.41). Among single complications, Asian children had a higher risk of developing feeding issues (OR, 2.07; 95% CI, 1.13–3.28). CONCLUSIONS AND RELEVANCE:. Ethnicity and socioeconomic deprivation may be linked to greater risk of certain complications after pediatric cardiac surgery. Further exploration of inequities is needed in this population.